2021
DOI: 10.3390/lubricants9080078
|View full text |Cite
|
Sign up to set email alerts
|

Tungsten Disulfide Inorganic Nanotubes Functionalized by PTFE for Friction Application

Abstract: Inorganic nanotubes (INTs) and fullerene-like nanoparticles (NPs) of WS2/MoS2 penetrate and exfoliate at the contact interface and facilitate tribofilm formation. While the tribological properties are greatly improved by exfoliated NPs that shed easily, they may be diminished by agglomeration in oil. Therefore, surface functionalization is employed to improve dispersion in oil-based suspensions. Here, WS2 INTs were functionalized by polytetrafluoroethylene (PTFE) in a simple and cost-effective bath sonication … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Zuo et al [196] effectively improved the abrasion resistance of polyethersulfone (PES)/PTFE-based polymers by using lamellar sodiummontmorillonite (NaMMT) as reinforcing filler, due to the load bearing of NaMMT on the worn surface. Levin et al [197] successfully enhanced the friction and wear reduction properties of WS 2 -inorganic nanotubes (INTs) with the addition of PTFE nanospheres using bath sonication. Abe et al [198] found that by incorporating proper amount SiO 2 nanoparticle dispersion into the polydopamine (PDA) underlayer, the durability of the PDA/PTFE coating can be improved by 70%, and this effect was attributed to the increased adhesion of the PTFE coating to the PDA underlayer.…”
Section: Polymers and Materials Modificationmentioning
confidence: 99%
“…Zuo et al [196] effectively improved the abrasion resistance of polyethersulfone (PES)/PTFE-based polymers by using lamellar sodiummontmorillonite (NaMMT) as reinforcing filler, due to the load bearing of NaMMT on the worn surface. Levin et al [197] successfully enhanced the friction and wear reduction properties of WS 2 -inorganic nanotubes (INTs) with the addition of PTFE nanospheres using bath sonication. Abe et al [198] found that by incorporating proper amount SiO 2 nanoparticle dispersion into the polydopamine (PDA) underlayer, the durability of the PDA/PTFE coating can be improved by 70%, and this effect was attributed to the increased adhesion of the PTFE coating to the PDA underlayer.…”
Section: Polymers and Materials Modificationmentioning
confidence: 99%
“…Additional efforts resulted in renewed synthesis of highly crystalline WS 2 and MoS 2 nanotubes in pure phase and scalable fashion. [5][6][7] The availability of these nanomaterials led to the investigation of their properties, and stimulated numerous applications in photoelectronics and nano-optics, [8][9][10] tribology, [11,12] and hydrogen storage. [13][14][15] Implantation of atoms into solid materials provides a way to modify their properties.…”
Section: Introductionmentioning
confidence: 99%